2000
DOI: 10.1093/ps/79.8.1204
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Transportation on Turkey Meat Quality

Abstract: Previous research has indicated that antemortem stress factors can influence the development of pale, soft, and exudative (PSE) meat in swine as well as in turkeys. Such antemortem factors can include environmental temperatures, relative humidity, preslaughter handling practices, and transportation. However, the effect of transportation on meat quality of turkeys has not been extensively studied. Eighty Nicholas male turkeys (21 wk of age) were divided into two groups and were either transported in coops on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 23 publications
6
43
1
5
Order By: Relevance
“…Mitchell and Kettlewell (1994) emphasise that the potentially harmful effects of adverse conditions during the transport are not only of political and public concern due to their consequences for animal welfare, but are also of economic importance with respect to increased losses and diminished quality of meat. A correlation between meat quality and exposure to preslaughter stress conditions has been demonstrated by Gregory (1996), Kannan et al (1997), Owens and Sams (2000), Taubert et al (2002), Debut et al (2003) and others. In addition, the stress associated with transporting poultry prior to slaughter has been shown to increase endogenic contamination and consequently aggravate the microbial risk for the consumer of poultry meat (Mengert and Fehlhaber 1996;Mengert et al 1998).…”
mentioning
confidence: 80%
“…Mitchell and Kettlewell (1994) emphasise that the potentially harmful effects of adverse conditions during the transport are not only of political and public concern due to their consequences for animal welfare, but are also of economic importance with respect to increased losses and diminished quality of meat. A correlation between meat quality and exposure to preslaughter stress conditions has been demonstrated by Gregory (1996), Kannan et al (1997), Owens and Sams (2000), Taubert et al (2002), Debut et al (2003) and others. In addition, the stress associated with transporting poultry prior to slaughter has been shown to increase endogenic contamination and consequently aggravate the microbial risk for the consumer of poultry meat (Mengert and Fehlhaber 1996;Mengert et al 1998).…”
mentioning
confidence: 80%
“…Long duration transportation has been reported to result in physiological and metabolic changes (Yue et al, 2010;Zhang et al, 2009) and that can affect animal welfare, processing yield and meat quality (Owens and Sams, 2000;Dadgar et al, 2010;Petracci et al, 2010). More importantly, transport stress also causes higher chicken mortality, live weight loss and poor meat quality, which results in substantial economic losses to the poultry industry (Bianchi et al, 2005;Karaman, 2009;Chauvin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A 3 h transport decreased glycogen contents with an increase in lactate content in broilers breast muscle, accompanied with lower pH 24 h and higher drip loss, so transport induced negative changes on broiler breast meat quality could result from the glycolytic enhancement [30]. Savenije et al, Owens et al and Debut et al also found the similar results of glycogen contents in birds breast muscle [10,28,31]. However, the increasing transport time decreased the glycogen content of biceps femoris muscle, while that of the breast muscle did not change, possibly since the thigh muscle is involved in maintaining balance in the moving vehicle during transport [32].…”
Section: Transport Durationmentioning
confidence: 85%
“…This can alter the physiological states of animals and subsequently affect meat quality. Transport stress impacts on parameters of bird physiological responses, like corticosterone (CORT), glucose and creatine kinase (CK) before slaughter [6][7][8] and thus has an effect on meat quality indices such as meat color and water holding capacity (WHC) [9,10]. According to these indicators, we can evaluate the stress level of poultry, so as to improve the management of transport conditions to meet the needs of poultry [6].…”
Section: Introductionmentioning
confidence: 99%